Evaluating bempedoic acid for the treatment of hyperlipidaemia. (1st February 2017) - Penson, Peter; McGowan, Mary; Banach, Maciej
ABSTRACT: Introduction: Despite the effectiveness of statins in the treatment of lipid disorders, residual risk still exists, and hitherto studies where additional drugs were added to statin therapy have been mainly negative or the outcomes were very modest. Therefore there is still a need for new and effective oral agents in the combination therapy of lipid disorders. Areas covered: The review covers the current state of knowledge on the mechanism of action of bempedoic acid (ETC-1002) and results from recent clinical studies. Expert opinion: ETC-1002 is a novel oral lipid-lowering therapy. The reduction of both low-density lipoprotein cholesterol (LDL-C) and high sensitivity C-reactive protein (hsCRP) demonstrated by ETC-1002 in clinical trials suggests that agent may have the potential for CV risk reduction. Adverse effects of current lipid-lowering agents can be dose-limiting, and combination approaches to lipid-lowering may often be utilized for optimal CV risk reduction. Because of this, new lipid-modulating drugs are urgently required. ETC-1002 has a unique mechanism of action (adenosine triphosphate-citrate lyase inhibition). It has been shown to be safe in combination with statins as well as ezetimibe, and appears to effectively lower LDL-C and has the potential to reduce the risk of muscle-related adverse events, which can limit the utilization and effectiveness of statin therapy.